A new species and one new record of Pallidogramme (Ascomycota, Graphidaceae) from Southern China - Jiang, Shu-Hao; Liang, Wen-Qi; Li, Su; Jia, Ze-Feng (Phytotaxa, 2026)
Comprehensive morphological, anatomical and chemical analyses support the recognition of an additional species in the genus Pallidogramme, which is described herein as new to science under the name P. norstictica. Additionally, Pallidogramme divaricoides is newly reported from China. This study also summarizes the key characteristics of the known species worldwide.